LITERATURE STUDY OF THE E-BOOK BASED ON EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) AS THE MAIN SOLUTION TO IMPROVING SUSTAINABILITY AWARENESS - Sihombing, Rizky Agassy; Muslim, Muslim; Rahman, Taufik; Karimi, Amir (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
This study underscores the significance of E-books centered on Education for Sustainable Development (ESD) for junior high school students, highlighting the value of interactive and multidirectional learning resources to foster sustainability awareness. The research objectives are to (1) find out the necessity of ESD-based E-books for enhancing sustainability awareness among students, 2) to prove the advantages and disadvantages of ESD-based learning compared to traditional learning, and (3) compare ESD-based learning with traditional methods. Using interviews, and literature study, the study finds traditional printed science textbooks insufficient in engaging students, often reducing their enthusiasm for learning. Interviews reveal that conventional textbooks are the primary learning medium, but students find them uninspiring. E-books, however, show promise in boosting student engagement through features like accessibility, searchability, and interactivity. Challenges exist in integrating ESD into the curriculum, primarily due to educators' limited understanding of sustainability concepts. Nonetheless, ESD-based E-books are seen as effective tools for developing a sustainable culture and enhancing students' awareness of sustainability issues. The literature study indicates a clear need for ESD-based E-books for students, emphasizing their role in preparing the next generation for sustainable development. The study recommends rigorous testing and comparative analysis of STEM-ESD E-books versus traditional resources to evaluate their effectiveness in raising sustainability awareness among junior high school students. The ultimate aim is to promote self-directed learning and greater awareness of sustainability.